The Body of Los Angeles, Between Commodity and Identity - Charles Joseph (Angles)
Los Angeles has mostly been studied in geographical or urban terms for the past fifty years in order to try and decipher a cityscape that had never been encountered on American soil before. Stemming from these studies, the LA school led by Edward Soja and his Postmodern Geographies experimented on new theoretical tools for this unprecedented space to be made sense of, tools that propelled the inhabitants to the center. Soja structured his thought according to his “trialectics of being” which is composed equally of spatiality, historicality and sociality (Soja 71). In doing so, the cultural factor became inherent to the analysis of urban environment, a posture which is the starting point of this paper. Focusing on the body in Los Angeles is a bilateral task as the body influenced, if not built, Los Angeles, while, the city, once established, shaped the body of its inhabitants on a physical and representational level. Taking into account emblematic cultural productions or practices rooted in Los Angeles, this paper intends to explore and analyze the closed-circuit generated between the Southern Californian megalopolis and the body in urban, corporeal and representational terms.